IoT based Hydroponic Monitoring System - Jayeta Das , Paras Chawla , Gagan Jot (International Journal of Advanced Science and Technology, 2020)
Vertical farming is the process of growing vegetation in vertically assembled layers, in this system land can be used more efficiently and can be implemented in an indoor environment. The major idea of vertical farming is to make a technology in which all the environmental factors that are suitable for plant growth can be controlled. In Vertical farming, various modern organic farming techniques are being used like hydroponics, aeroponics or aquaponics. The hydroponic system of farming is a fascinating method that uses a lesser amount of land. In hydroponic system, crops are grown-up using a nutrient solution mixed in water and without the use of soil. In this project, an automated hydroponic system is made by the implementation of IoT(Internet of Thing) to provide a controlled environment for the plants. The major function of this project is to make a system that uses IoT devices to monitor various factors like temperature, humidity, pH of nutrient solution, CO2 content in the air, total dissolved solution(TDS), and intensity of LED lights. To make the system easy to control, an android application is used to control IoT devices through a web browser on mobile phones and other handheld or compact devices. With this development, monitoring of the hydroponic system has become easier and plant growth can be looked after from time to time with no worker at the event.